Lean resource management and reliable interaction for a low-carbon-oriented new grid - Liu, Yuting (Frontiers in Energy Research, 2024)
The lean resource management and reliable interaction of massive data are important components of a low-carbon-oriented new grid. However, with a high proportion of distributed low-carbon resources connected to a new grid, issues such as data anomalies, data redundancy, and missing data lead to inefficient resource management and unreliable interaction, affecting the accuracy of power grid decision-making, as well as the effectiveness of emission reduction and carbon reduction. Therefore, this paper proposes a lean resource management and reliable interaction framework of a middle platform based on distributed data governance. On this basis, a distributed data governance approach for the lean resource management method of the middle platform in the low-carbon new grid is proposed, which realizes anomalous data cleaning and missing data filling. Then, a data storage and traceability method for reliable interaction is proposed, which prevents important data from being illegally tampered with in the interaction process. The simulation results demonstrate that the proposed algorithm significantly enhances efficiency, reliability, and accuracy in anomalous data cleaning and filling, as well as data traceability.